Mediating effect of expected service relationship between audit service quality and customer satisfaction: A study of Malaysian venture capital firms - Ismail, Ashari; Bakri, Mohammed Hariri; Md Razak, Mohamad Idham (Academic Inspired Network, 2020)
The scandal of Arthur Andersen and Enron should be a crucial lesson for audit firms concerning failure in audit service quality. Nevertheless, there are none of the audit firms can guarantee that the audit firms will maintain forever, and one of them will make no mistakes. The contention for audits for big audit firms as synonymous with quality audit has become questionable. The universal objective of the study was to analyze the cause and effect of expected service between audit service quality and customer satisfaction for Malaysian venture capital firms registered with KLSE. The study employed a descriptive study design and entailed the 65 listed venture capital firms as the population, because of the small member. Raw data were collected by the use of a structured questionnaire by use of drop and pick later. The collected data were analyzed first by use of descriptive statistics; correlation analysis was done to establish the mediating effect of the expected service relationship between the dependent and independent variables, and lastly, a regression analysis was executed on the model to test the hypotheses. The study supposes and expects that only two out of five audit quality dimensions (i.e., Assurance, Empathy, Reliability, Responsiveness, and Tangible) were statistically significant related to customer satisfaction. Thus the two characteristics of tangibility and responsiveness have a substantial impact on customer satisfaction. The research will be meaningful to the management of the venture capital firms and the audit firms alongside the academics who may want to pursue the subject further.